New insights into DNA polymerase mechanisms provided by time-lapse crystallography. (December 2022) - Weaver, Tyler M.; Washington, M. Todd; Freudenthal, Bret D.
Abstract: DNA polymerases play central roles in DNA replication and repair by catalyzing template-directed nucleotide incorporation. Recently time-lapse X-ray crystallography, which allows one to observe reaction intermediates, has revealed numerous and unexpected mechanistic features of DNA polymerases. In this article, we will examine recent new discoveries that have come from time-lapse crystallography that are currently transforming our understanding of the structural mechanisms used by DNA polymerases. Among these new discoveries are the binding of a third metal ion within the polymerase active site, the mechanisms of translocation along the DNA, the presence of new fidelity checkpoints, a novel pyrophosphatase activity within the active site, and the mechanisms of pyrophosphorolysis.